Causes of Illicit Love in The Last Kiss Movie (2006) Directed By Tony Goldwyn : A Psychoanalytic Approach - SUPATMI, SUPATMI (2012)
The problem statement of this study is what are causes of illicit love in The Last Kiss movie directed by Tony Goldwyn. The object of the research is the movie entitled The Last Kiss movie, directed by Tony Goldwyn published in 2006. The researcher uses Sigmund Freud psychoanalytic approach theory. The study belongs to qualitative study in which the writer uses two data sources namely primary data source and secondary data source. The primary data source is The Last Kiss movie itself and the secondary data source is the other source related to analysis such as the biography, books of literary theory and also psychological book, particularly related to the psychoanalytic theory of Sigmund Freud. The methods of data collecting are library research. The technique of data analysis is descriptive analysis. From the analysis, it can be drawn some conclusions. Firstly, the elements of the movie present a good unity. They consist of narrative element and technical elements of the movie. Secondly, the personality of Michael influences his id to do something under unconscious. As the work of ego, Michael fulfills the id demand. Nevertheless, his superego can differentiate what true and false are.